2016
DOI: 10.1080/02699931.2016.1189882
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced conflict-driven cognitive control by emotional arousal, not by valence

Abstract: Emotion is widely agreed to have two dimensions, valence and arousal. Few studies have explored the effect of emotion on conflict adaptation by considering both of these, which could have dissociate influence. The present study aimed to fill the gap as to whether emotional valence and arousal would exert dissociable influence on conflict adaptation. In the experiments, we included positive, neutral, and negative conditions, with comparable arousal between positive and negative conditions. Both positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
4
29
4
Order By: Relevance
“…Our results replicate and extend the findings of Zeng et al (2017) who demonstrated that emotional arousal manipulated at a block-level increases conflict adaptation. Our results clearly show that this effect of arousal also occurred when emotion is manipulated at the trial-level, thus demonstrating that the induction of phasic emotional arousal is sufficient to increase conflict adaptation.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results replicate and extend the findings of Zeng et al (2017) who demonstrated that emotional arousal manipulated at a block-level increases conflict adaptation. Our results clearly show that this effect of arousal also occurred when emotion is manipulated at the trial-level, thus demonstrating that the induction of phasic emotional arousal is sufficient to increase conflict adaptation.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the hypothesis, conflict adaptation was increased by positive and negative emotional words compared to neutral words, irrespective of the between-subject factor valence. These findings extend the findings of Zeng et al (2017) that revealed increased conflict adaptation for emotional words in a blocked design that did not allow the disentanglement of the phasic and tonic effects of arousal. The present results show for the first time that phasic arousal elicited by emotional words increases conflict adaptation in the subsequent trial.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations